Pengaruh Tingkat Inflasi dan Tingkat Suku Bunga Terhadap Harga Saham Perusahaan Perbankan LQ45 di BEI - Steven Aldiansyah; Kendy Rey (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Testing and analyzing the influence of interest rates and inflation rates on share prices in bank companies listed on LQ45 in 2016-2022 is the aim of the research. The research used a purposive sampling technique to take samples, using monthly quantitative data involving 420 data from 5 banking companies listed on the LQ45 index. The research use secondary data from annual reports and the BI website. Linear regression analysis is used as an analysis technique. The result is that interest rates and inflation do not have a negative and significant effect on the share prices of banking companies included in LQ45 on the IDX.